H2CO3 ==> H^+ + HCO3^-
HCO3^- ==> H^+ + CO3^2-
Surely you know how to write the k1 and k2 expressions.
Write chemical equations and corresponding equilibrium expressions for each of the two ionization steps of carbonic acid
Write chemical equations for first ionization step of carbonic acid
write chemical equations for second ionization step of carbonic acid.
3 answers
What if I told you that I do not
K = (concentration of products)/(concentration of reactants) with each concentration raised to the power shown by the coefficient in the balanced equation. That's the general way to do it. Applied to H2CO3 it looks like this.
k1 = (H^+)(HCO3^-)/(H2CO3). In this case the coefficients are 1 do you don't need to add a power to any of the concentrations.
k2 = (H^+)(CO3^2-)/(HCO3^-). Same thing about exponents. Since they are 1 it is understood and the 1 need not be there.
k1 = (H^+)(HCO3^-)/(H2CO3). In this case the coefficients are 1 do you don't need to add a power to any of the concentrations.
k2 = (H^+)(CO3^2-)/(HCO3^-). Same thing about exponents. Since they are 1 it is understood and the 1 need not be there.